Atomic Solution of Third Order Fractional Abstract Cauchy Problem (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we find an atomic solution of the fractional abstract Cauchy problem of order three. The fractional derivative used is the conformable derivative. The main idea of the proofs are based on theory of tensor product of Banach space.
Keywords: Fractional derivatives; Abstract Cauchy problem; Atom function; Conformable derivatve; Tensor product of Banach space